Proteolytic Activation of Plant Membrane-Bound Transcription Factors - De Backer, Jonas; Van Breusegem, Frank; De Clercq, Inge (Frontiers in Plant Science, 2022)
Because of the presence of a transmembrane domain, the subcellular mobility plan of membrane-bound or membrane-tethered transcription factors (MB-TFs) differs from that from their cytosolic counterparts. The MB-TFs are mostly locked in (sub)cellular membranes, until they are released by a proteolytic cleavage event or when the transmembrane domain (TMD) is omitted from the transcript due to alternative splicing. Here, we review the current knowledge on the proteolytic activation mechanisms of MB-TFs in plants, with a particular focus on regulated intramembrane proteolysis (RIP), and discuss the analogy with the proteolytic cleavage of MB-TFs in animal systems. We present a comprehensive inventory of all known and predicted MB-TFs in the model plant Arabidopsis thaliana and examine their experimentally determined or anticipated subcellular localizations and membrane topologies. We predict proteolytically activated MB-TFs by the mapping of protease recognition sequences and structural features that facilitate RIP in and around the TMD, based on data from metazoan intramembrane proteases. Finally, the MB-TF functions in plant responses to environmental stresses and in plant development are considered and novel functions for still uncharacterized MB-TFs are forecasted by means of a regulatory network-based approach.